(NnEMECKAQ [KOLA PENIQ(B.s (Nu^EBNOE POSOBIE(B.s - (N`LIUS gEJs; (Na(B.(Ni(B.(NiGNATOWI^(B.s (NPEREWOD^IKs ((NmOSKWAs (NlANXs (NpLANETA mUZYKI(B.s, 2024)
(N`LIUS gEJ (B-(NREFORMATOR WOKALXNOGO ISKUSSTWA(B. (NoN STAL AWTOROM BOLX[OGO ORIGINALXNOGO WOKALXNO(B-(NPEDAGOGI^ESKOGO SO^INENIQ NAPISANNOGO W DUHE U^ENIQ wAGNERA(B.s
Keywords: (NwOKALs